The Application of Government Accounting Standards in Social Service Financial Reports - Wulandari, Wulandari; Rahmadani, Ika (Institut Bisnis dan Informatika Kesatuan, 2024)
Good government is a government that is responsive, free from corruption, collusion and nepotism (Korupsi, Kolusi dan Nepotisme/KKN) and has good performance. Good governance can also be assessed from accountability, transparency and participation in every work result. Government Accounting Standards (Standar Akuntansi Pemerintahan/SAP) are a set of technical guidelines that regulate accounting principles, methods, procedures and practices that must be applied by government entities in preparing financial reports. Good financial reports have the following characteristics relevant, reliable, comparable, understandable. This research was conducted at the Suka Makmur social service, this research used descriptive qualitative methods. The location of the research was the Suka Makmur social service. The data used in this research is primary data obtained from interviews and observations. The data analysis technique used is the Miles Huberman model, namely data reduction, data presentation and drawing conclusions. The results of this research state that the implementation of government accounting standards in Suka Makmur social services makes the quality of financial reports better.